Os métodos autocompositivos e o exercício de uma nova política jurisdicional : um olhar crítico a partir da audiência do artigo 334 do código de processo civil - Damasceno, Marina (2018)
The present dissertation aims to analyze the jurisdictional policies that assist in the construction of a consensus culture. In order to do so, it critically investigates the propositions used in the preliminary hearing of conciliation or mediation brought by the Civil Procedure Code of 2015 (CPC/15). From a deductive approach method, starting from the ideas related to the transformation occurred in the society and, consequently, going through the consolidation of new forms to regulate litigation – adequate methods of conflicts resolution – concluding with the analysis of the preliminary hearing that aims the reach of consensus, foreseen in article 334 of the CPC/15. It can be concluded that a culture of consensus is not achieved by imposing a legal device, but through policies that effectively encourage its application, which cannot be restricted solely to the Judiciary. Therefore, the preliminary hearing, in essence, is beneficial to the realization of a jurisdictional policy, once it allows a consensual dialogue before a statement of defense is offered. If critically considered the models exposed by the legislator, there is a distortion in its arguments, which in article 334 prioritize the reduction of numbers through a legal imposition, thereby becoming indifferent or even harmful its application, as it ends up being considered only a mere procedural step.